A dinâmica do crescimento do perímetro cefálico em recém-nascidos pré-termo com peso ao nascer menor que 2000 gramas (do nascimento à idade corrigida de 42 semanas) - Glaucia Maria Moreira Galvao (2007)
A hundred and two newborn infants were studied longitudinally with the purpose of evaluating the growing dynamics of the head growth in preterm newborns, younger then 37 weeks, with weight at birth less than 2000 g from birth to 42 weeks of corrected age. The study was conducted at the Maternidade Odete Valadares/ Fundação Hospitalar do Estado de Minas Gerais (FHEMIG), between October 2005 and March 2006. Theweight and head growth were evaluated through weekly measures allowing curves of somatic growth to be developed and which were adjusted by Count's polynomial function model. Through the derivative of the polynomial model, it is possible to obtain the absolute speed expressed in cephalic perimeter gain in centimeters per week andweight gain in grams per day. At birth, 8,8% (9/55) of female preterm infants presented growth restriction intra-uterus (below negative 2 z score). This growth index was worsened, for 37,3% (17/55) ofpreterm infants were below negative 2 z score at 40 weeks of corrected age (Kramer et al., 2001). At birth, 12,8% (13/47) of male preterm infants presented growth restriction intra-uterus (below negative 2 z score). This growth index was worsened, for 28,4% (18/47) of preterm infants were below negative 2 z score at 40 weeks of corrected age (Kramer et al., 2001). The evolution of cephalic perimeter growth showed that, with 40 weeks of corrected age, 77,8% (42/55) of the female children and 72,3% (34/47) of the male children had equal or greater values than the 50 percentual reference of the World Health Organization (WHO, 2007). Only one child (1%) was below the negative 2 z score. The graphic evolution of cephalic perimeter showed that, at the corrected age of 40 weeks, the curves of boys and girls adequate to gestational age coincides with the 50 percentual of National Center for Health Statistics (NCHS, 2000), and is placed between percentual 50 and 95 of the new WHO (2007) reference. To the younger children for gestational age, with 40 weeks of corrected age, the curves of females and males were between the percentuals 3 and 50 of the new WHO (2007) reference and much lower than the 50 percentual of NCHS (2000) reference. The discoveries of this study highlight the need of accompanying the newborn infants cephalic perimeter at hospitals and ambulatory and the binding right of children to be attended with the latest, proper and affordable technology available, and which could lead precociously to the necessity of new investments on health and care.